On the generation of Beurling type Carleman ultradifferentiable C_0-semigroups by scalar type spectral operators - Markin, M. V. (Methods of Functional Analysis and Topology, 2016)
A characterization of the scalar type spectral generators of Beurling type Carleman ultradifferentiable C_0-semigroups is established, the important case of the Gevrey ultradifferentiability is considered in detail, the implementation of the general criterion corresponding to a certain rapidly growing defining sequence is observed.